Penerapan Trend Moment Untuk Meramalkan Penjualan Produksi Kelapa Sawit Di Kebun Buntu Pane, Kabupaten Asahan - Sinaga, Hommy Dorthy Ellyany; Irawati, Novica (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
The objective of this research is to design an application for forecasting the sales production of oil palm by using the trend moment method where the result of the forecasting is expected to be able to help the company to forecast sales in the future so that later on, it can be useful for the companies owner in making company plans such as fertilizing the oil palm and other planning as well. This forecasting of sales production application is dekstop based by utilizing computer software and taking data sample from two different plantation locations. The result of the system testing is running well. The accuracy calculation by using APE (Absolute Percentage Error) method shows the forecast accuration result is 95.95%. The conclusion from this research shows that trend moment method which has been applied can be using to forecast sales production of oil palm on the next period effectively with high accuracy.